Neonatal hypoxic encephalopathy: Correlation between post-cooling brain MRI findings and 2 years neurodevelopmental outcome - Mohammed Rusli, Emilia Rosniza; Ismail, Juriza; Wei, Wong Saw; Ishak, Shareena; Jaafar, Rohana; Zaki, Faizah Mohd (Indian Journal of Radiology and Imaging, 2019)
Objective: This study aims to evaluate the magnetic resonance imaging (MRI) brain patterns among hypoxic-ischemic encephalopathy (HIE) babies who underwent post-cooling MRI brain as well as to correlate the post-cooling brain scoring with patient’s neurodevelopmental outcome at 2 years. Subjects and Methods: It was a retrospective cross sectional study carried out at a tertiary university hospital. Record of patients diagnosed with neonatal HIE from 2007 until 2016 who completed 72 h of cooling therapy and had MRI brain within 2 weeks of life were included in this study. A new scoring system by Trivedi et al. that emphasizes on subcortical deep gray matter and posterior limb internal capsule injury were utilized upon MRI assessment, using TW, T2W, and diffusion-weighted imaging (DWI) sequences. Cumulative MRI brain score was obtained and graded as none, mild, moderate, and severe brain injury. The MRI brain scoring was then correlated with patient’s 2 years neurodevelopmental outcome using Fisher’s Exact Test. Results: A total of 23 patients were eligible of which 19 term neonates were included. 13% of these neonates (n = 3) had mild MRI brain injury grading with 52.2% (n = 12) moderate and 34.8% (n = 8) severe. There was no significant correlation seen between MRI brain grading and developmental outcome at 2 years old (P > 0.05). Conclusion: There was no significant correlation between neonatal MRI brain injury grading and 2 years neurodevelopmental outcome. Nevertheless, the new MRI brain scoring by Trivedi et al. is reproducible and comprehensive as it involves various important brain structures, assessed from different MRI sequences.
Keywords: MRI brain scoring; neonatal hypoxic ischemic encephalopathy; post-cooling therapy